Extraction of leaves oil from fresh leaves by using microwave-assisted extraction (MAE) and ultrasonic-assisted extraction (UAE) methods - Calaelma Logys Imalia; Firman Simbolon; Hendra Hendra; Nilam Junita; Yolanda Natalia; Viola Nurfitri; Nurul Afifah Zahra; Sry Oktavianty Purba; Tresya Siti Harni Saragih; Shelty Aty Pribadi; Wika Atro Auriyani; Feerzet Achmad (Konversi, 2025)
Essential oils are natural chemical compounds that are volatile and have a distinctive aroma, which are produced by plants as part of their secondary metabolites. This study aims to examine the differences in % yield content, extract pH, color, FFA value, and essential oil structure of each sample. The main materials used in this study were several types of aromatic leaves, namely lemongrass, pandan, lime, and eucalyptus leaves. The methods used were Microwave-Assisted Extraction (MAE) and Ultrasound-Assisted Extraction (UAE). The essential oil with the highest yield value and a specific gravity close to the Indonesian National Standard (SNI) is analyzed using Fourier Transform Infrared Spectroscopy (FTIR). The eucalyptus leaf sample yielded the highest percentage with the MAE method, achieving a yield of 46 %. The FTIR analysis identified a broad absorption peak at 3257.7 cm⁻¹, indicating the presence of hydroxyl groups (-OH), which suggests alcohols or phenols and possible moisture contamination. Peaks at 2124.6 cm⁻¹ and 1744 cm⁻¹ reveal methylene (C-H) and carbonyl (C=O) groups, suggesting the presence of terpenoids and oxidized compounds like esters or ketones. Additional peaks at 1640 cm⁻¹ and 1013.8 cm⁻¹ and ether (C-O) groups, with the latter confirming the presence of 1,8-cineole in eucalyptus oil.